AN EMERGING MARINE BIOTECHNOLOGY: MARINE DRUG DISCOVERY - Nurrahmi Dewi Fajarningsih (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2012)
Marine natural resources offer an opportunity to discover a novel chemical diversity withinterest ing pharmacologically active compounds to treat many diseases such as cancer,inflammation, bacterial and parasitic infections, and many other diseases. Marine drug discoveryis a rising area in marine biotechnology. Several hits of marine-derived drug compounds wereapproved; two of them are Ziconotide and Trabectedin. In 2004, Ziconotide was approved as paintreatment drugs in the United States and Europe. Then, in 2007, Trabectedin was also approvedas anticancer drug in Europe. The main problem in marine drug discovery research is materialsupply problem. Up till now, strategies to overcome the problem are “Pharmaceutical aquaculture”of biologically active marine biota and chemical synthesis approach. Chemical synthesis approachis feasible solution to be used, especially when working with less complex structure of compounds.However, when working with structurally complex compounds where total or even semi synthesiswas very difficult to be provided, aquaculture can be a solution. Currently, the use of microbiology,biochemistry, genetic, bioinformatics, genomic and meta-genomic has been intensifying in orderto have a better result in marine natural product drug discovery. As chemical synthesis needs anexpensive investment of advanced technology and highly skilled human resources, thuspharmaceutical aquaculture is more practicable to overcome the material supply insufficiency inIndonesia. Up till now, many Indonesian marine bioprospectors have been working with culturablemarine microorganism to produce bioactive compounds and some others starting to work withgenomic and metagenomic-based drug discovery.